2020
DOI: 10.1262/jrd.2020-086
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid improves porcine early embryonic development by inhibiting the accumulation of reactive oxygen species

Abstract: Carnosic acid (CA), a natural catechol rosin diterpene, is used as an additive in animal feeds and human foods. However, the effects of CA on mammalian reproductive processes, especially early embryonic development, are unclear. In this study, we added CA to parthenogenetically activated porcine embryos in an in vitro culture medium to explore the influence of CA on apoptosis, proliferation, blastocyst formation, reactive oxygen species (ROS) levels, glutathione (GSH) levels, mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
0
5
1
Order By: Relevance
“…In contrast with our initial hypothesis, blood ROM was not affected by treatment. Those results are in contrast with previous in vitro studies that observed a lower accumulation of ROS when different cell lines were treated with carnosic acid [ 79 , 80 , 81 ]. de Oliveira, et al [ 33 ] found lower ROS concentrations when neuroblastoma cells were treated with carnosic acid during induced neurotoxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our initial hypothesis, blood ROM was not affected by treatment. Those results are in contrast with previous in vitro studies that observed a lower accumulation of ROS when different cell lines were treated with carnosic acid [ 79 , 80 , 81 ]. de Oliveira, et al [ 33 ] found lower ROS concentrations when neuroblastoma cells were treated with carnosic acid during induced neurotoxicity.…”
Section: Discussioncontrasting
confidence: 99%
“…IVC environments for embryos suffer from higher oxygen concentrations (Guérin et al, 2001) resulting in ROS accumulation and inhibition of embryonic development (Jamil et al, 2020). Therefore, suppressing ROS accumulation using antioxidants may improve the potential of the porcine early stage embryonic development (Jiang et al, 2018; Peng et al, 2020). In this study, OA supplementation increased GSH levels and reduced ROS accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, suppressing ROS accumulation using antioxidants may improve the potential of the porcine early stage embryonic development (Jiang et al, 2018;Peng et al, 2020). In this study, OA system of the embryo (Biswas et al, 2005;Hansen & Harris, 2015) and acts as an important indicator of antioxidant capacity (Lim & Luderer, 2018).…”
Section: Oa Ameliorates Mitochondrial Function During Early-stage Por...mentioning
confidence: 92%
“…The mitochondrial membrane potential is an indicator of mitochondrial function. Embryos with a high mitochondria membrane potential exert positive effects on developmental potential of porcine preimplantation embryos [ 42 ]. In this study, AN supplementation improved mitochondrial function by increasing mitochondrial content and mitochondrial membrane potential in porcine IVF embryos.…”
Section: Discussionmentioning
confidence: 99%